2014
DOI: 10.1371/journal.pone.0100707
|View full text |Cite
|
Sign up to set email alerts
|

Dominance of CTX-M-Type Extended-Spectrum β-Lactamase (ESBL)-Producing Escherichia coli Isolated from Patients with Community-Onset and Hospital-Onset Infection in China

Abstract: ObjectiveTo investigate CTX-M genotypes among extended-spectrum β-lactamase-producing Escherichia coli (ESBL-EC) isolated from patients with community-onset and hospital-onset infections in China, their clonality and the distribution of CTX-M variants in different specimens of community-onset and hospital-onset infections.MethodsESBL-EC isolates were collected from general hospitals from 2011 to 2012 in China. Broth microdilution method antimicrobial susceptibility testing of 16 antibiotics was performed. Clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
54
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 28 publications
6
54
2
1
Order By: Relevance
“…A recent Chinese hospital study of the main MLSTs associated with extended-spectrum ␤-lactamase (ESBL)-producing strains of E. coli harboring CTX-M-14, CTX-M-55, or CTX-M-15 genes reported that the most common STs were ST131 (14.6%), ST1193 (7.9%), ST405 (6.6%), ST69 (6.3%), and ST648 (6.3%) (21). Prior to this study, ST1193 was unreported in China and was not identified among ESBL (CTX-M-14 or CTX-M-15)-producing E. coli isolates from infections in Korea and uropathogenic E. coli strains in northwest England (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…A recent Chinese hospital study of the main MLSTs associated with extended-spectrum ␤-lactamase (ESBL)-producing strains of E. coli harboring CTX-M-14, CTX-M-55, or CTX-M-15 genes reported that the most common STs were ST131 (14.6%), ST1193 (7.9%), ST405 (6.6%), ST69 (6.3%), and ST648 (6.3%) (21). Prior to this study, ST1193 was unreported in China and was not identified among ESBL (CTX-M-14 or CTX-M-15)-producing E. coli isolates from infections in Korea and uropathogenic E. coli strains in northwest England (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it could be a useful tool in China and other countries where bla CTX-M-1 and bla CTX-M-9 gene clusters, among others, have been reported to be on the rise. 9,[31][32][33] For instance, these enzymes, with varying prevalence rates, have also been reported in many countries in the Asia-Pacific region. 34 Although CTX-M group enzymes emerged later compared with TEM and SHV types, they have spread worldwide and specific subgroups have been localized in different geographic regions.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, results from previous molecular studies have demonstrated that bla CTX-M1 is endemic and is present among ST131 or non ST131 clones in healthcare and community settings. [16][17][18][19] The bla CTXM1 was detected in the range of 4-32 ug/mL ceftazidime, although higher MIC was associated with MDR and presence of both bla CTXM1 and bla SHV genes. It has been demonstrated that bla CTXM1/14 and bla CTXM-15 genes cause high level of resistance to cefepime/ceftriaxone and ceftazidime, respectively.…”
Section: Discussionmentioning
confidence: 97%